Mesin Pencetak Pilus Menggunakan Screw Pendorong - Yunus, Muhammad Afdhal Yunus; Edilla; Akhyan, Amnur (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2023)
Pilus is one kind of fried food and the shape like cylinder with variety length of cuts. Pilus makes by wheat flour, eggs, salt, and water. In general, production of pilus still manually use human power to make and cut pilus. Therefore, this pilus machine was created to make it easier and faster for human to create pilus. This pilus machine use a 1-phase AC motor to spin screw press and DC motor used to spin the cutter blade. ATMega8535 functionate as a microcontroller to control the speed and duration of motor. The Screw press is specially design, so it can press the dough out with two different sides. This Pilus Machine has capacity to produce pilus average 6kg / hr. The average current of ac motor needs 6,11 A. Average percentage of initial dough result with pilus result is 90.8%. This pilus machine can produced pilus with a length of 1cm, 2cm, dan 3cm.